Percy jackson and the greek gods - Riordan, Rick; Bernstein, Jesse (Random House/Listening Library New York, 2014)
"A publisher in New York asked me to write down what I know about the Greek gods, and I was like, Can we do this anonymously? Because I don't need the Olympians mad at me again. But if it helps you to know your Greek gods, and survive an encounter with them if they ever show up in your face, then I guess writing all this down will be my good deed for the week. So begins Percy Jackson's Greek Gods, in which the son of Poseidon adds his own magic--and sarcastic asides--to the classics. He explains how the world was created, then gives readers his personal take on a who's who of ancients, from Apollo to Zeus. Percy does not hold back. "If you like horror shows, blood baths, lying, stealing, backstabbing, and cannibalism, then read on, because it definitely was a Golden Age for all that." Dramatic full-color illustrations throughout by Caldecott Honoree John Rocco make this volume--a must for home, library, and classroom shelves--as stunning as it is entertaining"-- Provided by publisher